Perilaku Birokrasi Tenaga Non ASN BAWASLU dalam Seleksi Penyelenggara Pemilihan Umum di Provinsi Gorontalo - Mahmud, Ramli; Hamim, Udin; Djaafar, Lucyane (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2024)
This study aims to describe the dynamics of involvement and bureaucratic behavior of non-ASN Bawaslu personnel in the selection of members of the general election organizing commissioners in Gorontalo Province. This study uses a qualitative method with a phenomenological approach. Data collection uses observation, interview and documentation techniques. Data analysis is carried out interactively through data reduction, data presentation and drawing conclusions. The results of the study show that the dynamics of involvement of non-ASN Bawaslu personnel in the selection of general election organizers is influenced by capacity, both professionalism and independence, affiliation with community organizations, and support in the form of political party recommendations. The behavior of the non-ASN Bawaslu bureaucracy in recruiting candidates for general election organizer commissioners can be assessed from the aspects of legitimacy, rational encouragement, attractiveness which is a source of inspiration, and consultation. Individual characteristics, including abilities, needs, experience, intelligence and talents possessed by non-ASN Bawaslu staff, dominate bureaucratic behavior in the arena of contestation for recruitment of general election organizers.